Case Report: Pancreatic metastasis of renal cell carcinoma 16 years after nephrectomy - Lou, Yidan; Guo, Kaibo; Zheng, Song (Frontiers in Oncology, 2023)
Background: Renal cell carcinoma (RCC) is the most common renal malignancy, which may metastasize to different site in the body via hematogenous and lymphomatous routes. The pancreas is a rare metastatic site of metastatic RCC (mRCC), and isolated pancreatic metastasis of RCC (isPMRCC) is even rarer. Result: The present report describes a case of isPMRCC that recurred 16 years after surgery. The patient responded well to the treatment with pancreaticoduodenectomy and systemic therapy, and no recurrence was recorded after 2 years. Conclusions: isPMRCC is a distinct subgroup of RCC with unique clinical characteristics that may be explained by the underlying molecular mechanisms. Surgery and systemic therapy confer survival benefits to patients with isPMRCCs, although the recurrence problem has to be paid attention to.